[Pt(SCN)4]2–‐Based Coordination Polymers and Supramolecular Squares: Intermolecular Pt···H–C Interactions Probed by Luminescence Spectroscopy at Variable Pressure. Issue 22 (19th May 2017) - Suffren, Yan; Kobayashi, Masayuki; Ovens, Jeffrey S.; Rodrigue‐Witchel, Alexandre; Genre, Caroline; Sakai, Ken; Reber, Christian; Leznoff, Daniel B.
Abstract: Invited for the cover of this issue are the groups of Christian Reber from Université de Montréal and Daniel Leznoff from Simon Fraser University, Canada. The cover image shows the variation of the luminescence of a coordination polymer in response to pressure. Abstract : Thanks to the structural diversity accessible to coordination polymers, unprecedented effects can be achieved by varying the temperature and pressure to tune the luminescence… Read more about the story behind the cover in the Cover Profile and about the research itself on page 2865 ff (DOI:10.1002/ejic.201700149 ).